Faktor Penentu Penerimaan Devisa di Provinsi Bali: Analisis Partial Adjustment Model - Sanjaya, Putu Krisna Adwitya; Dewi, Made Heny Urmila; Dewi, Ni Putu Martini (Universitas Pendidikan Ganesha, 2020)
For a country whose exports are very limited, the government is always trying to find other sources that can be expected to increase the country's foreign exchange income. Such is the case with the Province of Bali. One effort to increase foreign exchange earnings is to develop tourism as a strategic core in order to create investment and accelerate economic growth. The research objective is to determine the effect of the number of foreign tourist visits, length of stay of tourists, export volumes of handicraft commodities and foreign exchange earnings in the previous year on foreign exchange earnings in Bali simultaneously and partially. This research uses the times series data 1994-2019 with the Partial Adjustment Model method. This study found the fact that the number of foreign tourist visits, the length of stay of tourists, the volume of exports of handicraft commodities and foreign exchange earnings in the previous period had a significant effect simultaneously on foreign exchange earnings in Bali Province. Partially, the volume of exports of handicraft commodities and foreign exchange earnings in the previous year had a positive and significant effect on foreign exchange earnings in the Province of Bali during the analysis period, while the length of stay of tourists did not significantly influence foreign exchange earnings in the Province of Bali in 1994-2019. Local Governments need to take concrete policies regarding the handling of the problem of foreign exchange earnings, for the coming period should the variables raised in this study need to be considered as strategic real indicators that affect foreign exchange earnings. Increased foreign exchange earnings should be strived to be absorbed in all sectors to accelerate the growth and economic development of Bali in order to realize a prosperous society.